(untitled) (Research, Society and Development, 2021)
This study aims to conduct a literature survey about the Nursing care in the prevention of skin lesions in premature newborns in a neonatal intensive care unit. This is na integrative literature review, the search occurred in the Virtual Health Library (VHL), with the help of the databases Latin American and Caribbean Literature on Health Sciences (LILACS), Nursing Database (BDENF), MEDLINE and Scientific Eletronic Library Online (SciELO). The articles were collected may to june 2021. Were used the following descriptors: Nursing, Skin, Premature newborn, and neonatal intensive care unit. After applying the inclusion citeria, 11 studies remained. Nursing care for premature newborns must be carried out continuously and cautiously, in view of that the RNPT needs special and delicate assistance, where the nurse as a health professional must always seek appropriate strategies to carry out a care that directly influences their assistance, with a view to offering more quality of life to premature infants in the NICU.